Effects of High-Intensity Interval Training vs. Sprint Interval Training on Anthropometric Measures and Cardiorespiratory Fitness in Healthy Young Women - Naves, João Pedro A.; Viana, Ricardo B.; Rebelo, Ana Cristina S.; de Lira, Claudio Andre B.; Pimentel, Gustavo D.; Lobo, Patrícia Cristina B.; de Oliveira, Jordana C.; Ramirez-Campillo, Rodrigo; Gentil, Paulo (Frontiers in Physiology, 2018)
Purpose: To compare the effects of 8 weeks of two types of interval training, Sprint Interval Training (SIT) and High-Intensity Interval Training (HIIT), on anthropometric measures and cardiorespiratory fitness in healthy young women. Methods: A randomized clinical trial in which 49 young active women (age, 30.4±6.1 years; body mass index, 24.8±3.1 kg.m-2; peak oxygen consumption (VO2peak), 34.9±7.5 mL.kg-1.min-1) were randomly allocated into a SIT or HIIT group. The SIT group performed four bouts of 30 s all-out cycling efforts interspersed with four minutes of recovery (passive or light cycling with no load). The HIIT group performed four bouts of four-minute efforts at 90–95% of peak heart rate (HRpeak) interspersed with three minutes of active recovery at 50–60% of HRpeak. At baseline and after eight weeks of intervention, waist circumference, skinfolds (triceps, subscapular, suprailiac, abdominal and thigh), body mass and BMI were measured by standard procedures and cardiorespiratory fitness was assessed by cardiorespiratory graded exertion test on an electromagnetically braked cycle ergometer. Results: The HIIT and SIT groups improved, respectively, 14.5±22.9% (P<0.001) and 16.9±23.4% (P<0.001) in VO2peak after intervention, with no significant difference between groups. Sum of skinfolds reduced 15.8±7.9% and 22.2±6.4% from baseline (P<0.001) for HIIT and SIT groups, respectively, with greater reduction for SIT compared to HIIT (P<0.05). There were statistically significant decreases in waist circumference (P<0.001) for the HIIT (-3.1±1.1%) and SIT (-3.3±1.8%) groups, with no significant difference between groups. Only SIT showed significant reductions in body weight and BMI (p<0.05). Conclusions: Eight weeks of HIIT and SIT resulted in improvements in anthropometric measures and cardiorespiratory fitness, even in the absence of changes in dietary intake. In addition, the SIT protocol induced greater reductions than the HIIT protocol in the sum of skinfolds. Both protocols appear to be time-efficient interventions, since the HIIT and SIT protocols took 33 and 23 minutes (16 and 2 minutes of effective training) per session, respectively.